HEALTH LITERACY AND PATIENT AUTONOMY: DOES AGE MATTER?. (11th November 2018) - Shotwell, J; Dunlap, B; Mungenast, J; Renzi-Hammond, L
Abstract: Health literacy, or the ability to obtain, process, synthesize, and apply health information, and health autonomy, or the extent to which one desires to exercise control over decisions are independently known to influence health outcomes. Older adult populations tend to have the lowest levels of health literacy and health autonomy. The extent to which health literacy and health autonomy are related is not known. The extent to which these relationships affect health outcomes in older adult patients is also not known. As a first step in addressing these gaps, a racially and ethnically diverse sample of adult patients at a community vascular clinic in the Southeastern United States was recruited for participation. A total of 73 patients (age range 18 – 88 years, median age = 63, M = 60.97, SD = 15.30) completed questionnaires assessing health literacy and health autonomy prior to medical visits at the clinic. Moderate and statistically significant positive correlations (r = 0.40) between health literacy and patient autonomy were detected. Trends for older adult patients (r = 0.39, p = 0.35) tended to match the larger sample in magnitude. These findings suggest that health literacy and autonomy are related and that this relationship is robust in the older adult population. Interventions targeting health literacy do not tend to also target health autonomy, and vice versa. The extent to which interventions focusing on improving health literacy simultaneously enhance levels of autonomy is unknown, and should be explored.